Routledge handbook of modern Chinese literature - Gu, Ming Dong 1955-; Feng, Tao (Routledge, 2019)
The Routledge Handbook of Modern Chinese Literature presents a comprehensive overview of Chinese literature from the 1910s to the present day. Featuring detailed studies of selected masterpieces, it adopts a thematic-comparative approach. By developing an innovative conceptual framework predicated on a new theory of periodization, it thus situates Chinese literature in the context of world literature, and the forces of globalization. Each section consists of a series of contributions examining the major literary genres, including fiction, poetry, essay drama and film. Offering an exciting account of the century-long process of literary modernization in China, the handbook's themes include: Modernization of people and writingRealism, rmanticism and mdernist astheticsChinese literature on the stage and screenPatriotism, war and revolutionFeminism, liberalism and socialismLiterature of reform, reflection and experimentationLiterature of Taiwan, Hong Kong and new mediaThis handbook provides an integration of biographical narrative with textual analysis, maintaining a subtle balance between comprehensive overview and in-depth examination. As such, it is an essential reference guide for all students and scholars of Chinese literature
Keywords: Chinese literature / 20th century / History and criticism; Chinese literature / 21st century / History and criticism; Literatur; Chinesisch; Aufsatzsammlung